Interview ES (Karakul Circulations: Colonial Economies and the Un_Making of Disciplinary Knowledges in Germany and Namibia, 2020)
1 WAV and 1 mp3 audio file of interview
Keywords: Karakul sheep; History; Herding; Sheep-shearing; Postcolonialism; South Africa; Agriculture; Colonisation; Namibia; Swakara; Karakul Circulations; Colonial Economies; Karakul Farming; Germany; Colonial South-West Africa; German Colonialism; Karakul Sheep Industry